2022
DOI: 10.3389/fcimb.2022.775535
|View full text |Cite
|
Sign up to set email alerts
|

Predominant Bacterial and Viral Otopathogens Identified Within the Respiratory Tract and Middle Ear of Urban Australian Children Experiencing Otitis Media Are Diversely Distributed

Abstract: BackgroundOtitis media (OM) is one of the most common infections in young children, arising from bacterial and/or viral infection of the middle ear. Globally, Streptococcus pneumoniae and non-typeable Haemophilus influenzae (NTHi) are the predominant bacterial otopathogens. Importantly, common upper respiratory viruses are increasingly recognized contributors to the polymicrobial pathogenesis of OM. This study aimed to identify predominant bacteria and viruses in the nasopharynx, adenoids and middle ears of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“… 2 It was recently reported that non-typeable Haemophilus influenzae and rhinovirus were common bacterial and virus pathogens within the upper respiratory tract of peri-urban/urban South-East Queensland Australian children with and without otitis media. 6 Previously, we have reported that 73% and 69.7% of S. pneumoniae and H. influenzae were identified among school children with AOM in Banyumas Regency, Central Java, Indonesia respectively. 7 , 8 Data on the spectrum of viruses that cause AOM in Indonesia are still limited.…”
Section: Introductionmentioning
confidence: 94%
“… 2 It was recently reported that non-typeable Haemophilus influenzae and rhinovirus were common bacterial and virus pathogens within the upper respiratory tract of peri-urban/urban South-East Queensland Australian children with and without otitis media. 6 Previously, we have reported that 73% and 69.7% of S. pneumoniae and H. influenzae were identified among school children with AOM in Banyumas Regency, Central Java, Indonesia respectively. 7 , 8 Data on the spectrum of viruses that cause AOM in Indonesia are still limited.…”
Section: Introductionmentioning
confidence: 94%
“…Specifically, AOM induced by NTHi has been associated with recurrence. In about one-third of instances, recurrent chronic AOM might increase the likelihood of developing chronic suppurative otitis media (CSOM) [3].…”
Section: Genesmentioning
confidence: 99%
“…Encapsulated strains are divided into six serotypes (A to F), sharing relative similarity irrespective of their serotype. Conversely, non-encapsulated strains exhibit genetic diversity [3].…”
mentioning
confidence: 99%
“…Contribution to disease by each pathogen varies by study and detection method [see ( Tamir et al, 2023 ] for review of recent reports of microbiology of OM). The viruses that are commonly associated with OM include respiratory syncytial virus (RSV), coronaviruses, influenza viruses, adenoviruses, human metapneumovirus, human bocavirus, and picornaviruses ( Pettigrew et al, 2011 ; Ngo et al, 2022 ). The most commonly associated pathogens with CSOM are Staphylococcus aureus and Pseudomonas aeruginosa ( Afolabi et al, 2012 ; Khattak et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%